REORGANIZATION OF THE FERGANA VALLEY FOR THE NEEDS OF AGRICULTURE IN 1941-1942. (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article analyzes the reorganization of agriculture in the Fergana Valley during the early years of World War II to adapt to wartime conditions, as well as the challenges faced in fulfilling state production plans. It highlights the extensive involvement of elderly people, women, and children in agricultural labor to compensate for men conscripted to the frontlines, the introduction of new crop varieties, and the economic difficulties encountered in the agricultural sector.